New records of the East-Asian Nemoura species (Plecoptera: Nemouridae) for South of the Russian Far East with description of the larvae - Teslenko, Valentina A. (Zootaxa, 2016)
Three species of the Nemoura, N. jejudoensis Zwick & Baumann, 2011 and N. jilinensis Zhu & Yang, 2003, and N. tripotini Zwick, 2010 are reported in the South of the Russian Far East for the first time. The larvae of the three species are described and illustrated. The larvae were associated with adults by rearing or by preemergent male larva. The main diagnostic features of the larvae are based on the differences in the chaetotaxy the pronotum, legs, abdominal, and cercal segments.